Imperial childhoods and Christian mission education and emotions in South India and Denmark - Vallgårda, Karen 1980- (Houndmills [u.a.] Palgrave Macmillan, 2015)
Children and the Discordance of Colonial Conversions -- Controversy and Collapse : On Christian Day Schools -- Raising Two Categories of Children -- Tying Children to God with Love -- Science, Morality, Care, and Control -- Emotional Labor of Loss -- Planting Seeds in Young Hearts -- Epilogue: The Productive Figure of the Universal Child -- Appendix 1: Glossary -- Appendix 2: Overview over Mission Stations -- Bibliography: Unpublished Sources -- Bibliography: Literature
"Like other Christian missionaries operating throughout the colonized world, the Danish Evangelicals who traveled to India in the late nineteenth and early twentieth centuries invested remarkable resources in the upbringing and education of children. At the same time as they sent most of their own children back to Denmark, they took South Indian children into their care. Through an extensive literary production, they also sought to educate children in Denmark about the 'heathen' world. From the perspective of the Indo-Danish mission encounter, Imperial Childhoods and Christian Mission examines the heavy ideological weight that different categories of children in India and Denmark were made to carry in both local and imperial politics. Employing a postcolonial history of emotions approach, Karen Vallgårda documents the centrality of emotional labor to the changing imagination of childhood. This book reassesses general assumptions about the history of childhood within the Western world by probing its entanglements with broader imperial developments. It suggests that interactions between transnational actors in different parts of the colonized world contributed to the contemporary emotional and scientific reconfiguration of childhood. Furthermore, it shows how projects of rescuing 'brown' children from their parents and societies helped portray imperialism as a benevolent and justified endeavor"--
Includes bibliographical references
Archivierung/Langzeitarchivierung gewährleistet
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Missions, Danish -- History -- India, South; Tamil (Indic people) -- Missions -- History; Poor children -- Education -- History -- India, South; Children of missionaries -- Education -- History -- Denmark; Christian Education -- History -- India, South; Christian Education -- History -- Denmark; Evangelicalism -- Social aspects -- History -- India, South; Imperialism -- Religious aspects -- Christianity -- History; HISTORY / Asia / India & South Asia; HISTORY / Modern / 19th Century; HISTORY / Modern / 20th Century; HISTORY / Europe / Scandinavia; RELIGION / Christian Ministry / Children; India, South -- Social conditions; Denmark -- Social conditions